2020
DOI: 10.1124/dmd.120.000039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microbiome on Hepatic Metabolizing Enzymes and Transporters in Mice during Pregnancy

Abstract: The microbiome and pregnancy are known to alter drug disposition, yet the interplay of the two physiologic factors on the expression and/or activity of drug metabolizing enzymes and transporters (DMETs) is unknown. This study investigated the effects of microbiome on host hepatic DMETs in mice during pregnancy by comparing four groups of conventional (CV) and germ-free (GF) female mice and pregnancy status, namely, CV nonpregnant, GF non-pregnant, CV pregnant, and GF pregnant mice. Transcriptomic and targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…CYP2C19 activity in humans is known to decrease during pregnancy [36]. Our previous study also showed downregulation of Cyp2c50 in pregnancy, regardless of the microbiome status [12]. Cyp2c50 plays an important role as arachidonic acid epoxygenase and is considered a major metabolizing enzyme for the production of epoxyeicosatrienoic acids (EETs) [37].…”
Section: Plos Onementioning
confidence: 93%
See 4 more Smart Citations
“…CYP2C19 activity in humans is known to decrease during pregnancy [36]. Our previous study also showed downregulation of Cyp2c50 in pregnancy, regardless of the microbiome status [12]. Cyp2c50 plays an important role as arachidonic acid epoxygenase and is considered a major metabolizing enzyme for the production of epoxyeicosatrienoic acids (EETs) [37].…”
Section: Plos Onementioning
confidence: 93%
“…Details of the animal studies were the same as previously described [ 12 ]. Briefly, all animals (pregnant and non-pregnant mice) were maintained with the same autoclaved diet, non-acidified water, and autoclaved bedding.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations